2017
DOI: 10.1021/acsami.7b12814
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Mobile Two-Dimensional Electron Gases with a Strong Gating Effect at the Amorphous LaAlO3/KTaO3 Interface

Abstract: Two-dimensional electron gas (2DEG) at the perovskite oxide interface exhibits a lot of exotic properties, presenting a promising platform for the exploration of emergent phenomena. While most of the previous works focused on SrTiO-based 2DEG, here we report on the fabrication of high-quality 2DEGs by growing an amorphous LaAlO layer on a (001)-orientated KTaO substrate, which is a 5d metal oxide with a polar surface, at a high temperature that is usually adopted for crystalline LaAlO. Metallic 2DEGs with a Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 43 publications
6
80
0
1
Order By: Relevance
“…Since this large MR is rare in oxide 2DESs, we summarize the typical MR ratios for different oxide‐based conducting interfaces or surfaces (note that the MR ratio is highly sample‐, temperature‐, and magnetic field‐dependent, we therefore just summarize MR at 8 T below 5 K, which is accessible for most transport facilities), as shown in Figure . It is obvious that the MR ratio of the GAO/STO interface is higher than the other oxide interfaces, including LAO/STO, [ 42,57–63 ] CaZrO 3 /SrTiO 3 (CZO/STO), [ 64,65 ] LaTiO 3 /SrTiO 3 (LTO/STO), [ 66 ] amorphous‐LAO/KTaO 3 (a‐LAO/KTO), [ 43,67 ] Sr 3 Al 2 O 6 /STO (SAO/STO), [ 12 ] extrinsic STO conducting surface, [ 54,68,69 ] and even bulk STO. [ 27,70,71 ] Based on the substantial MR above, a general qualitative picture could be constructed: MR ratio has a close relationship with the mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Since this large MR is rare in oxide 2DESs, we summarize the typical MR ratios for different oxide‐based conducting interfaces or surfaces (note that the MR ratio is highly sample‐, temperature‐, and magnetic field‐dependent, we therefore just summarize MR at 8 T below 5 K, which is accessible for most transport facilities), as shown in Figure . It is obvious that the MR ratio of the GAO/STO interface is higher than the other oxide interfaces, including LAO/STO, [ 42,57–63 ] CaZrO 3 /SrTiO 3 (CZO/STO), [ 64,65 ] LaTiO 3 /SrTiO 3 (LTO/STO), [ 66 ] amorphous‐LAO/KTaO 3 (a‐LAO/KTO), [ 43,67 ] Sr 3 Al 2 O 6 /STO (SAO/STO), [ 12 ] extrinsic STO conducting surface, [ 54,68,69 ] and even bulk STO. [ 27,70,71 ] Based on the substantial MR above, a general qualitative picture could be constructed: MR ratio has a close relationship with the mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of KTaO 3 , surface 2DEGs have been reported in ultrahigh vacuum conditions from oxygen vacancies [33,34]. Since these reports, a variety of means have been developed to produce interfacial 2DEGs in KTaO 3 , primarily through the introduction of polar/non-polar interfaces [35,36,37]. These interfaces have exhibited such interesting properties as optically tunable Rashba effect and greater Hall mobility than analogous LaAlO 3 /SrTiO 3 interfaces.…”
Section: Overview Of Complex Oxide Thin Films and Interfacesmentioning
confidence: 99%
“…It has been reported that conductivity tuning with light illumination is possible for KTO. [ 47,48 ] Only a few reports on the photoconductivity of oxygen vacant conducting KTO are available. [ 49 ] But the effect on the electrical conductivity of 2DEG in KTO under light and/or gate is not well explored.…”
Section: Introductionmentioning
confidence: 99%